Tattoos, desire and violence marks of resistance in literature, film and television - Beeler, Karin 1963- (McFarland, 2006)
"This book explores the tattoo in the context of resistance and marginality, and draws attention to the important relationship between the visual and the narrative components of tattoo culture. Tattoos are examined in relation to Holocaust victims, slaves and colonized peoples, gangs and inmates, and other societies"--Provided by publisher.
"This book explores the tattoo in the context of resistance and marginality, and draws attention to the important relationship between the visual and the narrative components of tattoo culture. Tattoos are examined in relation to Holocaust victims, slaves and colonized peoples, gangs and inmates, and other societies"--Provided by publisher.
Includes bibliographical references and index
Keywords: Tatouage - Aspect social; Tatouage au cinéma; Tatouage dans la littérature; Tatouage à la télévision; Gesellschaft; Tattooing in literature; Tattooing in motion pictures; Tattooing on television; Tattooing -- Social aspects; Tätowierung -- Motiv; Tätowierung; Film; Literatur